Role of the C-Terminal Domain of the Alpha Subunit of RNA Polymerase in LuxR-Dependent Transcriptional Activation of the lux Operon during Quorum Sensing - Finney, Angela H. (American Society for Microbiology, 2002)
During quorum sensing in Vibrio fischeri, the luminescence, or lux, operon is regulated in a cell density-dependent manner by the activator LuxR in the presence of an acylated homoserine lactone autoinducer molecule [N-(3-oxohexanoyl) homoserine lactone]. LuxR, which binds to the lux operon promoter at a position centered at −42.5 relative to the transcription initiation site, is thought to function as an ambidextrous activator making multiple contacts with RNA polymerase (RNAP). The specific role of the α-subunit C-terminal domain (αCTD) of RNAP in LuxR-dependent transcriptional activation of the lux operon promoter has been investigated. The effects of 70 alanine substitution variants of the α subunit were determined in vivo by measuring the rate of transcription of the lux operon via luciferase assays in recombinant Escherichia coli. The mutant RNAPs from strains exhibiting at least twofold-increased or -decreased activity in comparison to the wild type were further examined by in vitro assays. Since full-length LuxR has not been purified, an autoinducer-independent N-terminally truncated form of LuxR, LuxRΔN, was used for in vitro studies. Single-round transcription assays were performed using reconstituted mutant RNAPs in the presence of LuxRΔN, and 14 alanine substitutions in the αCTD were identified as having negative effects on the rate of transcription from the lux operon promoter. Five of these 14 α variants were also involved in the mechanisms of both LuxR- and LuxRΔN-dependent activation in vivo. The positions of these residues lie roughly within the 265 and 287 determinants in α that have been identified through studies of the cyclic AMP receptor protein and its interactions with RNAP. This suggests a model where residues 262, 265, and 296 in α play roles in DNA recognition and residues 290 and 314 play roles in α-LuxR interactions at the lux operon promoter during quorum sensing.